ASSESSMENT OF VIRGIN COCONUT OIL (VCO) WITH GATE-TO-GATE LIFE CYCLE ASSESSMENT ANALYSIS APPROACH - Giovanni Ruly Putra; Reifaldy Tsany Betta Aryanto; Syifaurrahmah Syifaurrahmah; Yesaya Emeraldy Priutama; Mega Mutiara Sari; I Wayan Koko Suryawan (Matriks Teknik Sipil, 2022)
VCO or Virgin Coconut Oil is a high-quality crude oil extract formed from coconut without chemical compound addition or high-temperature heating. The differences between VCO and other coconut oil are commercial coconut oil produced from copra or dried coconut meat. Life Cycle Assessment (LCA) is a method used to assess a product based on its lifespan, starting from extracting raw materials for the product to the industrial manufacturing process to product distribution. This LCA aims to implement zero waste on VCO Production by using wasted coconut water in some product that has economic value. We suggest a solution for coconut water waster with two alternatives, namely nata de coco production and coconut shell charcoal. Options to improve environmental quality were selected based on wastewater parameters and the resulting CO2 equivalent.